Advertisement Remove all ads

Solve: (4-3"X")/5 + (7 - "X")/3 + 4 1/3 = 0 Hence, Find the Value of 'P', If 3p - 2x + 1 = 0 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

Solve: `(4-3"x")/5 + (7 - "x")/3 + 4 1/3 = 0` Hence, find the value of 'p', if 3p - 2x + 1 = 0

Advertisement Remove all ads

Solution

`=> (4-3"x")/5 + (7 - "x")/3 + 4 1/3 = 0`


`=> (4-3"x")/5 + (7 - "x")/3 +  13/3 = 0`


`(12 - 9"x" + 35 - 5"x" + 65 = 0)/15`  ...(L.C.M. of 5, 3, 3 = 15)

-14x + 112 = 0

⇒ -14x = -112

⇒ x = `(-112)/-14` = 8

Hence x = 8

Now, 3p – 2x + 1=0

⇒ 3p – 2 x 8 + 1 = 0

⇒ 3p – 16 + 1 =0

⇒ 3p – 15 = 0.

⇒ 3p=15

⇒ p = 5

Concept: Solving Linear Inequations
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (A) | Q 25 | Page 166
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×